2020
DOI: 10.22454/fammed.2020.964431
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity in Primary Care: Patient Perception and Preferences

Abstract: Background and Objectives: Screening for and addressing food insecurity in primary care may improve associated comorbidities. The purpose of this study was to explore patient attitudes regarding screening for food insecurity and to elicit patient preferences for intervention in a primary care setting. Methods: Patients (N=284) completed a brief, voluntary survey in a university-based clinic and two community-based clinics over a 5-month period. Respondents were classified as either food-secure or food-insecure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…A review of FI screening programs based in US hospitals, clinics, and health centers found that most programs received funding from multiple short-term sources, with several program managers expressing concern about long-term sustainability [ 100 ]. FI screening is also not yet standard clinical practice despite evidence indicating food-insecure patients appreciate being screened and referred to resources [ 101 ]. Analysis of Food for Families (a hospital-run program that connects food-insecure patients with SNAP, WIC, and food pantries) found that participants experienced moderately improved blood pressure, suggesting an association between referral to aid programs and better cardiovascular health [ 102 ].…”
Section: Knowledge Gaps Opportunities For Interventions and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of FI screening programs based in US hospitals, clinics, and health centers found that most programs received funding from multiple short-term sources, with several program managers expressing concern about long-term sustainability [ 100 ]. FI screening is also not yet standard clinical practice despite evidence indicating food-insecure patients appreciate being screened and referred to resources [ 101 ]. Analysis of Food for Families (a hospital-run program that connects food-insecure patients with SNAP, WIC, and food pantries) found that participants experienced moderately improved blood pressure, suggesting an association between referral to aid programs and better cardiovascular health [ 102 ].…”
Section: Knowledge Gaps Opportunities For Interventions and Future Directionsmentioning
confidence: 99%
“…Implementing patient navigation teams can help patients apply for SNAP, WIC, and other benefits ( Fig. 3 ) [ 100 , 101 ]. Some clinics also provide medically-tailored meals and fruit and vegetable “prescriptions” (usually vouchers or coupons to be redeemed at farmers markets or food pantries), which can further help patients obtain nutritious foods that suit their treatment and improve their cardiovascular risk profile [ 100 ].…”
Section: Knowledge Gaps Opportunities For Interventions and Future Directionsmentioning
confidence: 99%
“…While screening for food insecurity does not exist in the Australian health care setting, screening exists in health care settings in other countries, where it has been found to be part of a successful approach when seeking to address food insecurity [51][52][53]. Both the American Academy of Family Physicians, and the American Academy of Paediatrics recommend that food insecurity is routinely screened [54].…”
Section: Institutional Level Solutionsmentioning
confidence: 99%
“…Specifically, there was a disconnect in the acknowledgement of FI and the knowledge of resources and community organizations that offer programs and services to address FI [ 69 , 81 ]. A recent study by Runkle and Nelson in 2021 [ 81 ] found family medicine and pediatric physicians expressed concern over the stigma associated with discussing FI in the clinic; however, another study by Kopparapu and colleagues in 2020 [ 82 ] showed that 83.9% of primary care patients stated that asking about FI was important and 82.7% felt it demonstrated that the clinic cared about their well-being. Another important consideration is a patient’s preferences for FI screening.…”
Section: Screening For Food Insecuritymentioning
confidence: 99%
“…Another important consideration is a patient’s preferences for FI screening. Kopparapu and colleagues [ 82 ] also identified that primary care patients preferred having a nurse ask the screening questions, and Palakshappa and colleagues [ 83 ] found that patients preferred a written questionnaire versus a face-to-face screening method [ 82 , 83 ]. These challenges represent opportunities for future research to design interventions that target FI training, screening uptake, and closed-loop referral management with tracking of local resources…”
Section: Screening For Food Insecuritymentioning
confidence: 99%